Modelo de trabajo en equipo intelectual en grupos organizacionales: una revisión conceptual (A model of intellectual teamwork in organizational groups: a conceptual review) - Mendoza Gómez, Joel; Rositas Martínez, Juan (UANL. Facultad de Contaduría Pública y Administración, 2013)
Abstract. In this conceptual study, the perspective of performance results of a team is studied, considering as the unit of analysis, the individual behavior within the organizational natural group in the context of knowledge or intellectual work. To explain the effectiveness of the performance of the group are utilized processes and emergent states identified as teamwork. Thus, it is built and proposed a theoretical model that establishes the relationship between variables such as productivity, trust in the group, group affective tone, backup behaviors, psychological security, and identification with the group. In building the model, a literature review that incorporates the definitions and the antecedents of the relations between the variables is utilized. In this structure, a number of assumptions that are the result of this conceptual work are derived.